Ability of sodium copper chlorophyllin complex to repair photoaged skin by stimulation of biomarkers in human extracellular matrix - McCook JP; Stephens TJ; Jiang LI; Law RM; Gotz V (Clinical, Cosmetic and Investigational Dermatology, 2016)
John P McCook,1 Thomas J Stephens,2 Lily I Jiang,2 Robert M Law,3 Vincent Gotz4 1Discovery Partners LLC, Frisco, 2Thomas J. Stephens & Associates, Inc., Richardson, 3ProPath, Dallas, TX, 4MDRejuvena, Inc., San Diego, CA, USA Purpose: To examine the effect of sodium copper chlorophyllin complex on the expression of biomarkers of photoaged dermal extracellular matrix indicative of skin repair.Patients and methods: Following a previously published 12-day clinical assessment model, skin biopsy samples from the forearms of four healthy females with signs of photoaged skin were obtained and samples were analyzed by immunohistochemistry for key biomarkers of aging skin after each subject was treated with a test material consisting of a gel containing a liposomal dispersion of sodium copper chlorophyllin complex 0.05%, a positive control of tretinoin cream 0.025%, and an untreated negative control.Results: There was a statistically significantly greater amount of fibrillin/amyloid P and epidermal mucins found for skin treated with the test material containing 0.05% sodium copper chlorophyllin complex and the reference control tretinoin 0.025% cream compared to the negative control (untreated site). Expression of procollagen 1 and dermal mucin also showed a greater presence in the samples treated with the test material and the reference control compared to the negative control, though the differences were not statistically significant. No adverse events were observed or reported by the subjects during the course of the study.Conclusion: The results of this human biopsy study suggest that both retinoids and sodium copper chlorophyllin complex have beneficial effects on biomarkers of photoaged skin. Products containing both sodium copper chlorophyllin complex and retinols may provide a dual approach to reversing age-related decreases in hyaluronic acid (HA) in the skin: inhibition of the breakdown of HA via sodium copper chlorophyllin complex by inhibition of hyaluronidase, and stimulation of HA synthases by retinol. Keywords: hyaluronic acid, glycosaminoglycans, retinoid, hyaluronidase, mucins